Experimental Rnomics: Towards The Identification And Characterization Of Non-Protein-Coding Ribonucleic Acids In Pathogenic Agent, Salmonella Typhi - Zakaria, Robaiza (2008)

(untitled)
RNA bukan-pengkod-protein (npcRNA) merupakan satu kelas pengawalatur-ribo yang bertindak di dalam bentuk kompleks RNA-protein (sebagai RNPs) didalam pelbagai laluan pengawalaturan. Tesis ini memberikan tumpuan ke atas_ pengenalpastian npcRNA secara eksperimental daripada bakteria patogenik Salmonella enterica serovar Typhi (S. Typhi), penyebab penyakit demam kepialu. Melalui pendekatan RNomiks Eksperimental, 82 calon novel npcRNAdaripada perpustakaan cDNA S. Typhi telah dikenalpasti dan dicirikan. Daripada jumlah ini, 28 telah ditranskrip daripada IGR, 29 ditranskrip di dalam arah antisense kepada ORF dan 18 dikenalpasti bertindihan dengan ORF. Sementara 7 calon yang lain telah ditranskIlp daripada kawasan repititif dan beberapa kedudukan bukan repitatif yang lain. Sebelas npcRNA merupakan npcRNAs yang telahpun dilaporkan. Non-protein-coding RNA (npcRNA) is a large class of riboregulators that act in complex with proteins (as RNPs) in diverse regulatory pathways. This thesis focused on the experimental identification of small npcRNAs from Salmonella enterica serovar Typhi (s. Typhi), the aetiological agent of typhoid fever. By an Experimental RNomics approach, 82 species of uncharacterized novel npcRNA candidates were identified from library generated from different growth phases of a clinically isolated S. Typhi. From this, 28 were transcribed from the IGRs, 29 were transcribed in the antisense orientation of the ORFs and 18 were identified to overlap the ORFs. Another 7 candidates were transcribed from repetitive regions and several non-repetitive locations. Eleven known npcRNAs were also detected.